Perkembangan Tari Tirik Lalan Masyarakat Banjar di Tembilahan, Provinsi Riau - Dini Rahdatul Aisy; Wahida Wahyuni; Eva Riyanti; Suaida Suaida (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine and describe the development of the Tirik Lalan Dance among the Banjar community in Tembilahan, Riau Province. Tirik Lalan Dance is a traditional paired dance characteristic of the Banjar ethnic group who migrated to Tembilahan through trade routes. Over time, this dance has undergone choreographic development due to interaction with the local Malay culture. This study uses a qualitative method with a descriptive analytical approach, and is analyzed using the Cultural Development Theory by Linton, the Cultural Ecology Theory by Steward, and the Choreography Theory by Y. Sumandio Hadi. Data was collected through literature study, observation at Sanggar Citra Sebati, in-depth interviews with traditional artists, and documentation. The results of this study show that development occurred in three main elements of presentation, namely movement, music, and costume. The movements that were originally straightforward and open as typical of Banjar developed into more subtle, closed, and symbolic forms, adapting to Islamic values and Malay aesthetics, such as the integration of Malay salutation and soft steps resembling Zapin. The accompanying music developed with variations of the gambus and accordion. Meanwhile, the dancers' costumes transitioned from Baju Kurung Basisit to Kebaya Labuh and Songket with Pucuk Rebung motifs. This development proves a dynamic cultural adaptation without eliminating the original philosophical values of the dance.